2013
DOI: 10.1002/esp.3364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrophobicity on splash erosion of model soil particles by a single water drop impact

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…In this work we consider droplets hitting dry soil, which is both wettable and firm enough to maintain its porous structure during the impingement. When droplets have an impact on powder surfaces or granular layers [40][41][42][43][44] , we did not observe bubble formation during the drop impingement. We speculate that if the porous media deform considerably during impact there are low permeability paths for air to escape from beneath the droplet and so it is not trapped.…”
Section: Resultsmentioning
confidence: 58%
“…In this work we consider droplets hitting dry soil, which is both wettable and firm enough to maintain its porous structure during the impingement. When droplets have an impact on powder surfaces or granular layers [40][41][42][43][44] , we did not observe bubble formation during the drop impingement. We speculate that if the porous media deform considerably during impact there are low permeability paths for air to escape from beneath the droplet and so it is not trapped.…”
Section: Resultsmentioning
confidence: 58%
“…While no changes occurred in this study, changes would be expected in cases where soil heating is more excessive, which would increase the complexity of the environmental processes occurring in this farming system. Among the principal effects of soil water repellency are changes in aggregate stability and enhancement of splash erosion of small particles (Ahn et al, 2013;Fox et al, 2007), a change in infiltration rate (Doerr et al, 2009), and a reduction in the topsoil strength, which can lead to rill initiation (DeBano, 2000).…”
Section: Soil Moisture and Water Repellencymentioning
confidence: 99%
“…The higher S c in the transition season can be explained by the effect of SWR in soil surface. According to Ahn et al (2013), soil water repellency increases the distance of ejection of particles after a drop impact, which in hillslopes with a certain degree of inclination involves greater net downslope movement and, hence, net erosion of particles. Shakesby et al (2000) reported that in hydrophilic soils the wetting provoked an increase in the particles cohesion and, in consequence, a compact surface seal that limited the amount of splashed sediments was developed.…”
Section: Sediments and Soil Lossmentioning
confidence: 99%